Experimental and theoretical divulging of electronic structure and optical properties of Zn-doped SnSe thermoelectric materials. (15th March 2023) - Singh, K.; Dubey, P.; Joshi, P.K.; Kumar, K.; Choudhary, B.L.; Arora, G.; Ahuja, B.L.; Mishra, S.K.
Abstract: Electron momentum densities (EMDs) of undoped and Zn-doped SnSe are measured using a 100 mCi 241 Am Compton spectrometer. Various density functional theories and hybrid exchange and correlation potentials (LDA, PBE, PBEsol, PBE0, and B3LYP) within the linear combinations of atomic orbitals (LCAO) calculations have been attempted to compute Compton profiles (CPs) and electronic structure of the doped and undoped SnSe. Among all the Compton line shapes predicted using first principles, B3LYP approximation-based EMDs are found to be in a better reconciliation with the CP measurements. Experimental data is also analyzed in terms of localization of Zn-d states. Going beyond the LCAO method, the density of state (DOS), energy bands, reflectance, dielectric constant, and absorption coefficient for Zn-doped (Sn0.97 Zn0 .03 Se and Sn0.95 Zn0 .05 Se) and undoped SnSe are computed using the FP-LAPW-mBJ method. It is seen that Sn-5s and Se-4p orbitals are responsible for the formation of the indirect band gap. Interestingly, Zn doping in SnSe (Sn0.97 Zn0 .03 Se and Sn0.95 Zn0 .05 Se) leads to interstitial bands in the low energy side of the conduction region leading to electron trapping centres and reduction of band gap (from 0.816 to 0.508eV in case of FP-LAPW-mBJ scheme and 1.152 to 0.510 eV in case of LCAO-B3LYP scheme). Our works evidently support the positive effect of Zn doping in enhancing the electronic and thermoelectric properties of the SnSe by forming interstitial bands. Apart from this, undoped and Zn-doped SnSe can also be used for solar cells as an absorber material and detection of ultraviolet (B and C) rays. Due to the formation of interstitial bands induced trapping centres, Zn-doped SnSe can also be uniquely employed in thermoluminescence devices (TLDs). Highlights: First-ever experimental Compton profiles of undoped and Zn-doped SnSe. Suggested hybrid exchange and correlation potentials for deducing EMDs and various properties. Reported interstitial energy bands, DOS and optical response using FP-LAPW-mBJ method. Explored plausibly the trapping centres for thermoluminescence applications (in TLDs). Anticipated definite use in optoelectronic and thermoelectric devices due to interstitial bands.